An Ergonomic and Economic Analysis of the Implementation of a Multifunctional Folding Chair at CV. Fixed Interior - Saputra, Yonanda Rasyid; Santoso, Ivan Septiawan; Nugroho, Dony Satriyo (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
This study aims to analyze the ergonomic and economic aspects of implementing a multifunctional folding chair at CV. Fixed Interior, Semarang. The research addresses the high risk of non-ergonomic working postures and low time efficiency due to insufficient supporting facilities in the production environment. A comparison of working time before and after chair implementation was conducted, along with an economic feasibility analysis. Ergonomic assessments utilized the Rapid Upper Limb Assessment (RULA) and Rapid Entire Body Assessment (REBA), while the economic evaluation employed Net Present Value (NPV), Internal Rate of Return (IRR), Break-Even Point (BEP), and Benefit-Cost Ratio (BCR). Results show a reduction in standard time from 678.31 minutes to 441.51 minutes, indicating a 35% efficiency increase. RULA and REBA scores reflected a lower posture risk level. Economically, the project is feasible, with an NPV of IDR 8,156,523, IRR exceeding the discount rate, BEP at five units sold, and a BCR of 14.15. Therefore, the folding chair is effective and commercially viable.